The role of visual ethnography in co-producing climate information services in cities - Buyana, Kareem; Walubwa, Jacqueline; Mukwaya, Paul; Sseviiri, Hakimu; Byarugaba, Disan; Nsangi, Gloria (Bristol University Press, 2025)
Diverse approaches to climate information services are emerging as impacts escalate in an urbanising globe. However, the climate information services involving cities are mainly collaborations with actors from science, multilateral, national and municipal authorities. There are limited efforts to build on knowledge from residents in local communities about risk and response options, to steer collaborations on climate information services. This article examines visual ethnography as an enabler of climate information services that connect societal and scientific objectives at local scales in cities. Based on case study findings from Kampala city in Uganda, local-level framings of climate risks and responses were grouped into exploratory and intersectional framings. The exploratory framings are risks and response options directly linked to Sustainable Development Goals (SDGs) 11 and 13 on cities and climate change respectively, while depicting some degree of contradiction. Intersectional framings are risks and response options demonstrating the interrelatedness of climate issues across different SDGs. Local communities do take on scientific information on impacts and adaptation barriers but also connect risks and responses to experiences of tested options, which sometimes only emerge during the process of visual ethnography and are not initially identified. Visual ethnography can be an important source of information not only on stressors experienced and priority actions by local communities, but can also be a climate solutions imagery, that contains positive adaptation stories with opportunities for enriching and complementing scientific inquiry on responses.